2008
DOI: 10.1088/0953-8984/21/3/035112
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of bismuth borate glasses

Abstract: Bismuth borate glasses with Bi(2)O(3) concentration of 20-66 mol% were prepared by melt quenching and devitrified by heat treatment above their glass transition temperatures. All glasses show a strong tendency towards crystallization on annealing that increases with Bi(2)O(3) concentration. The crystalline phases formed on devitrification were characterized by FTIR absorption spectroscopy and DSC measurements. Our studies reveal that phases produced in glasses are strongly determined by initial glass compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Intensity of this band increases with increase in Bi 2 O 3 concentration. It may be due to the Bi-O and Bi-O-Bi bonds in BiO 6 octahedra [20,21,[23][24][25].…”
Section: Xrd Analysismentioning
confidence: 99%
“…Intensity of this band increases with increase in Bi 2 O 3 concentration. It may be due to the Bi-O and Bi-O-Bi bonds in BiO 6 octahedra [20,21,[23][24][25].…”
Section: Xrd Analysismentioning
confidence: 99%
“…The modifier that allows very good optical properties of borate glasses to be obtained is bismuth oxide. Borate-bismuth glasses are characterized by high density and high refractive indices and, importantly due to their preparation, are glasses with a comparatively low melting point in a wide glass formation range (20–80 mol % Bi 2 O 3 ) [ 11 ]. The choice of bismuth oxide over lead oxide, which has often been used in glasses in recent years, seems particularly good, as it breaks down the toxic material while leaving the glass with the desired properties.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [12] has also reported two glass transitions in some metallic glasses. Bajaj and Khanna [13] has reported two separate phases in some crystallized bismuth borate glasses. In case of glasses containing two alkali species, mixed alkali effect has also been claimed [14] with the help of two-stage relaxation mechanism.…”
Section: Introductionmentioning
confidence: 99%